(untitled) (Surya Abdimas, 2025)
The purpose of this community service focusing on self-efficacy within the Pemuda Pintar community is to enhance confidence and motivation by: 1) fostering understanding and recognition of self-efficacy, 2) enabling participants to apply self-efficacy components to their situations, 3) clarifying the difference between growth and fixed mindsets, and 4) providing tips for developing self-efficacy. The event, organized by the Pemuda Pintar Community and the TSM Center for Research and Community Service, took place on Saturday, May 4, 2024, from 10:00 to 12:30 WIB via Google Meet. It involved 31 participants, a mix of students and workers. The resource person was a lecturer in human resource management from Trisakti School of Management, who also held a psychology degree. The session proceeded smoothly without major technical issues. To facilitate understanding, the presentation was designed to be clear and accessible. As a result, participants gained greater awareness of improving their self-efficacy, which can boost their self-motivation. Survey results indicated that about 78 percent of participants understood the material. Ultimately, this community service aims not only to increase knowledge but also to inspire behavioral changes and action plans among members of the Pemuda Pintar community. This community service activity is the second collaboration between the TSM Research and Community Service Center and the Eden Community. It is hoped that the Eden community, through Pemuda Pintar, can become sustainable, benefiting the community and helping them develop themselves.